Immunogenetics and clinical phenotype of sympathetic ophthalmia in British and Irish patients. Issue 3 (1st March 2001) - Kilmartin, Dara J; Wilson, David; Liversidge, Janet; Dick, Andrew D; Bruce, Julia; Acheson, Robert W; Urbaniak, Stanislaw J; Forrester, John V
Abstract : BACKGROUND/AIMS: Sympathetic ophthalmia (SO) is a classic example of autoimmune disease where human leucocyte antigen (HLA) genomic associations could provide further understanding of mechanisms of disease. This study sought to assess HLA genetic polymorphism in British and Irish patients with SO, and to assess whether HLA gene variants are associated with clinical phenotype or disease severity. METHODS: High resolution DNA based HLA typing using polymerase chain reaction sequence specific primers was performed in 27 patients with SO and 51 matched healthy controls. Clinical phenotype and markers of disease severity were determined prospectively in 17 newly diagnosed patients and from medical record review and repeat clinical examination in 10 previously diagnosed patients. RESULTS: HLA-Cw*03 (p=0.008), DRB1*04 (p=0.017), and DQA1*03 (p=0.014) were significantly associated with SO. For class II alleles at higher resolution, only HLA-DRB1*0404 (relative risk (RR) = 5.6, p = 0.045) was significantly associated with SO. The highest relative risk for any of the associated haplotypes was with HLA-DRB1*0404-DQA1*0301 (RR=10.9, p=0.019). Patients with the DRB1*04-DQA1*03 associated haplotype were significantly more likely to develop SO earlier, with fewer inciting ocular trauma events, and to require more systemic steroid therapy to control inflammatory activity. CONCLUSIONS: Sympathetic ophthalmia is associated with HLA-DRB1*04 and DQA1*03 genotypes in white patients, similar to Japanese patients. Differences in DRB1*04 gene variant associations (−0404 in Britain and Ireland and −0405 in Japan) may have implications for HLA peptide binding in disease initiation. The DRB1*04–DQA1*03 haplotype is a marker of increased SO susceptibility and severity, as in Vogt-Koyanagi-Harada disease, which also has similar clinicopathological and HLA associations.